“I Invest by Following Lead Investors!” The Role of Lead Investors in Fundraising Performance of Equity Crowdfunding - Shen, Tao; Ma, Jiangshui; Zhang, Bin; Huang, Wen; Fan, Fan (Frontiers in Psychology, 2020)
Psychological factors play a critical role in affecting investor decisions. This study explores how lead investors influence following investors psychologically, thus affecting fundraising performance of equity crowdfunding. We draw upon signaling theory and observational learning theory to argue that following investors could be induced to invest in a project if they observe the proportion of funding by lead investors in the funding target to be high, that the lead investors have rich investment experience, and that lead investors can offer help to the projects. To test our hypotheses, we analyze a sample of 215 projects from a Chinese equity crowdfunding platform. The results reveal that the proportion of lead investor investment in the funding target and their investment experience are positively related to fundraising performance. However, the help offered by lead investors towards the projects has no impact on funding performance. Theoretical and practical implications are discussed.